The Role of Counselors in Developing Guidance and Counseling Management in Schools - Miftahul Jannah; Neviyarni S; Yarmis Sukur (Quality : Journal Of Education, Arabic And Islamic Studies, 2024)
This article discusses the important role of counselors in developing a guidance and counseling management system in schools. Counselors have a fundamental role in fostering students to become academically, emotionally, morally, and spiritually mature individuals. The effectiveness of guidance and counseling programs is highly dependent on the implementation of effective and efficient management by counselors. Therefore, the application of guidance and counseling management principles, such as planning, organizing, implementing, supervising, and evaluating programs. These principles are very important to implement because they can help counselors carry out their duties optimally and achieve the goals of the guidance and counseling program that have been set. The approach to writing this article is a literature review, namely a written summary made by searching for materials from many sources of books, articles, and other documents. The results of this study are that good guidance and counseling management in each school is the main key to improving the quality of guidance and counseling services for students. Effective guidance and counseling services can help solve problems experienced by students and increase their learning motivation.